PELATIHAN PENGEMBANGAN KELAS ONLINE DAN PENILAIAN AUTENTIK MENGGUNAKAN MOODLE DI SMPIT LAA TAZHAN CITRA - Agustina, Noni; Lestari, Sri; Mustaqim, Karna; Chelsea, Chelsea; D, Yona; Selindah, Selindah (Universitas Esa Unggul, 2021)
Covid-19 pandemic impacts the learning which it shifts face-to-face learning to distance learning. The shift insists the schools, particularly teachers to apply the effective and efficient learning medium. The principal of SMPIT Laa Tazhan Citra mentioned his teachers need the effective, efficient, and interesting learning medium during Covid-19 situation. Besides, they need to develop their knowledge and skill to assess students’ tasks or performance effectively. Their needs could be facilitated through training of online class development and authentic assessment using Moodle. The methods undertaken were presentation, discussion, and simulation. The result showed that the training provided teachers insight, knowledge, and skill to build online class and authentic assessment using Moodle. They are expected to apply their knowledge and skills in their own class referring to their students’ need and characteristics as well their learning objectives. Keywords: online class, Moodle, authentic assessment, rubric